Hubungan Bullying dengan Kesehatan Mental pada Remaja di SMP Negeri 2 Blang Bintang - Inda Rahmani; Syukriadi Syukriadi; Syarifah Masthura (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
In Indonesia, mental health issues among adolescents are prevalent. Mental health of both victims and offenders is affected by bullying, and it could lead to ongoing mental health issues such as worry and sadness. The objective of this study is to investigate the connection between bullying and teenage mental health in SMP Negeri 2 Blang Bintang. The study was implemented from June 17 to June 19, 2025, using a cross-sectional design and a quantitative research methodology. A sample of 60 teenagers was chosen via proportional random sampling from the total population of 151 adolescents.The General Health Questionnaire-12 (GHQ 12) and the Olweus Bully/Victim Questionnaire (OBVQ) were the research tools utilized. The chi-squared test was used to evaluate the data. The findings revealed that out of 54 victims of bullying, the majority (48 individuals or 88.9%) had impaired mental health. Conversely, among 6 non-victims, most (5 individuals or 83.3%) did not have impaired mental health. The chi-square test indicated p = 0.001, meaning bullying victims and mental health are significantly correlated.. Additionally, among 49 bullying perpetrators, most (46 individuals or 93.9%) had impaired mental health, while among 11 non-perpetrators, most (8 individuals or 72.7%) did not have impaired mental health. The chi-square test also showed p = 0.001, indicating a strong correlation between the mental health of bullies and their behavior. The researchers recommend the importance of maintaining mental health and collaborating across various sectors to reduce bullying behavior.